NILAI-NILAI SEMASA DAN SETEMPAT DALAM PENENTUAN HUKUM: SATU PERBINCANGAN AWAL - Ali, Ab Karim (Jurnal Syariah, 2019)
The article is an attempt to elucidate the paramount importance of local and contemporary values (’urf) ill deriving ruling in Islam. Therefore, it tries to cover to the topic by explaining essential things such as concept, approches as well as limitations.